Character Mediation of Plot Structure: Toward an Embodied Model of Narrative - Tu, Carmen (My University, 2019)
The classic view of narrative since the time of Aristotle is that plot structure is prioritized over characters in defining the nature of stories. According to this view, plot is an abstract structure external to the protagonist, and the protagonist’s actions are determined by the thematic goals of the plot. The current analysis calls for a reversal in the prioritization of these elements in creating a story. We present an Embodied Plot model in which character not only drives plot, but embodies plot as well. According to this model, the dramatic arc of plots is attributable to psychological processes occurring in the protagonist’s mind. Plot structure is thus isomorphic with the psychological and problem-solving experience of the protagonist inside the storyworld. We apply this model to a number of fairy tales to demonstrate how the dramatic arc of these stories can be explained in each case by the protagonist’s experientiality.
Keywords: Plot; Narrative; Problem solving; Embodied; Character; Fairy tale